Гінодієція, мінливість та мікроеволюційні процеси в умовах тривалої інтродукції в Донецькому ботанічному саду НАН України на прикладі Majorana hortensis Moench. - Gorlacheva, Z.S. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2011)
The phenomenon gynodioecy and variability in morphological characters, vegetative and generative organs in the introduced samples Majorana hortensis Moench., obtained by seed reproduction during 24 years, have been studied. It has been determined that as a result of adaptation processes to environmental conditions the south-east of Ukraine and the availability of gynodioecy take place formation of a new form of M. hortensis, which is characterized by sustainability to the conditions of the region, morphological changes in the corolla and in crease the number of ovules. These changes are considered as the result of microevolutionary process.